The BRIICs and inequality: income inequality trends in major emerging markets and their implications - Fabisiak, Jan; Prokurat, Sergiusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
This paper seeks to study the trends in income inequalities in the BRIIC countries. The first section of this paper investigates the evolution of the understanding of income inequalities, moving on to their classification, measurement and proposed impact on growth. The following section examines the nature of the BRIIC countries, their commonalities, future perspectives on the world stage and, most importantly to this paper, their income inequality dynamics. The last section concludes with a cross-country comparison.

Artykuł bada trendy kształtowania się nierówności dochodowych w krajach BRIIC. Pierwsza część opisuje ewolucję pojmowania nierówności dochodowych, przechodząc do ich klasyfikacji, metod pomiaru i wpływu na wzrost gospodarczy. Kolejna część definiuje kraje BRIIC, ich cechy wspólne, ich przyszłe perspektywy w globalnym układzie sił, oraz, co najważniejsze z punktu widzenia tego artykułu, zmiany w ich nierównościach dochodowych. Ostatnia część podsumowuje debatę, przeprowadzając porównania między poszczególnymi krajami.